Exploring the Therapeutic Potentials of Exopolysaccharides Derived From Lactic Acid Bacteria and Bifidobacteria: Antioxidant, Antitumor, and Periodontal Regeneration - Khalil, Maha A.; Sonbol, Fatma I.; Al-Madboly, Lamiaa A.; Aboshady, Tamer A.; Alqurashi, Abeer S.; Ali, Sameh S. (Frontiers in Microbiology, 2022)
The metabolites of Lactic Acid Bacteria (LAB) and Bifidobacteria (Bb) have recently received a lot of attention due to their ability to protect interactions in blood and tissues, as well as their biodegradability and biocompatibility in human tissue. Exopolysaccharides (EPS) derived from bacteria have a long history of use in therapeutic and other industrial applications with no adverse effects. In this regard, EPSs were isolated and characterized from LAB and Bb culture supernatants to determine their antioxidant, antitumor, and periodontal regeneration properties. The antioxidant capacity of the EPSs varied with concentration (0.625–20 mg/ml). The highest antioxidant activity was found in LAB; Streptococcus thermophiles DSM 24731-EPS1, Lactobacillus delbrueckii subsp. bulgaricus DSM 20081T-EPS5, Limosilactobacillus fermentum DSM 20049-EPS6, and Bb; Bifidobacterium longum subsp. longum DSM 200707-EPS10. Human breast cancer cells (MCF7), colon cancer cells (CaCo2), human liver cancer cells (HepG2), and human embryonic kidney 293 (HEK 293) cells were used as controls to assess the antitumor properties of the selected EPSs. According to the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium-bromide (MTT) assay, EPS5 had the highest cytotoxicity against MCF7, CaCo2, and HepG2, with IC50 values of 7.91, 10.69, and 9.12 mg/ml, respectively. Lactate dehydrogenase (LDH) activity was significantly higher in cell lines treated with EPS5-IC50 values compared to other EPSs-IC50 values (P 0.05). RT-PCR results showed that EPS5 treatment increased Bax, Caspase 8, Caspase 3, and p53 gene expression. The expression of the BCL2, MCL1, and Vimentin genes, on the other hand, was reduced. The MTT test was used to examine the effect of EPS5 on the viability of human periodontal ligament fibroblast cells (hPDLFCs), and it was discovered that EPS5 increased hPDLFC viability. According to HPLC analysis, galactose made up 12.5 % of EPS5. The findings of this study pave the way for the use of EPS, which hold great promise for a variety of therapeutic purposes such as antioxidant, antitumor, and periodontal regeneration.